(untitled) (Research, Society and Development, 2021)
Objective: to evaluate the clinical conditions and therapeutic interventions that predispose the occurrence of AKI in patients admitted to the ICU. Method: it is a Systematic Literature Review in the following data sources: PUBMED, MEDLINE, LILACS, BDENF and SCIELO. The evidence from the studies was classified according to (XX). The following descriptors were used: “Hemodialysis” AND “Intensive care”. Results: it is noteworthy that ARF in the ICU is related to: risk factors associated with therapy (use of VAD, IMV, antibiotic therapy, drug-induced nephropathy and the use of iodine-based contrast); comorbidities (DM, SAH, pulmonary, digestive, liver, neoplasms, anemia, obesity and immunosuppression), acute conditions (trauma, hemorrhage, snakebite, shock, infection, sepsis, eclampsia; complications of cardiovascular disease, acute neurological disease, necrosis acute tubular syndrome, hepatorenal syndrome and accidents with venomous animals), age, hydroelectrolytic disorders (hypercalcemia, hypocalcaemia, hypernatremia and hyponatremia), disorders of basic acid balance, accumulative water balance and acute tubular necrosis. Conclusion: it appears that the AKI in the ICU has to do with the patient’s clinical condition and therapeutic interventions performed in the ICU.